Iroquoian Medicine Women and the Earth Around them in New York State - Moffett, Corrine A. (Kansas State University. Dept. of Hsitory, 2017)
The Iroquois Nation has a long history and valued reputation regarding their reverence for the environment; from traditions passed down orally for years to a 1999 study by the Seneca Nation in an effort to save their land. The medicine women of the Iroquois in New York state have a connection to the environment that is unique from other tribal members. Their domestic role as food preparers accompanied by their role as medicine women connects them to the environment around them. Using and analyzing primary narratives by outside observers and geographical studies, this examination takes a look into the lesser-studied aspects of the connection between Iroquoian medicine women and their environment.
Citation: Moffett, C. (2017). Iroquoian Medicine Women and the Earth Around them in New York State. Unpublished manuscript. Kansas State University, Manhattan, KS.
Keywords: Native American; Iroquios; Medicine Women; Environmental History; Upstate New York; Native American Women